Pertimbangan Hakim Menjatuhkan Hukuman Pidana Bersyarat terhadap Pelaku Tindak Pidana Narkotika - Jumadi Jumadi; Indrajaya Indrajaya (Universitas Batanghari Jambi, 2022)
Abstract One of the goals of criminal law is as a social institution that includes several things, namely as part of a social reaction when there is a violation of applicable norms. When the judge's decision by imposing a conditional criminal sentence on narcotics, it often invites debate and dissatisfaction from various parties. The problem of this journal is what is the basis for the judge's consideration of imposing a conditional criminal sentence and what are the inhibiting factors for the application of the judge's decision. This research is an empirical legal research that prioritizes field data using the analytical descriptive specification method. The results of the study that the judge's consideration of imposing a conditional sentence in a narcotics crime case at the Palembang Class IA District Court was based on juridical considerations (legal certainty), namely Article 14a to Article 14f of the Criminal Code, Article 127 paragraph (1) letter c of the Narcotics Law and sociological considerations and philosophical considerations. The inhibiting factors for applying conditional criminal penalties at the Class IA Palembang District Court are the law factor, law enforcement officers, infrastructure, and the cultural factor of the community itself.